Replication of single-stranded plasmid pT181 DNA in vitro. - Birch, P (1992)
Plasmid pT181 is a 4437-base-pair, multicopy plasmid of Staphylococcus aureus that encodes tetracycline resistance. The replication of the leading strand of pT181 DNA initiates by covalent extension of a site-specific nick generated by the initiator protein at the origin of replication and proceeds by an asymmetric rolling circle mechanism. The origin of the leading strand synthesis also serves as the site for termination of replication. Replication of pT181 DNA in vivo and in vitro has been shown to generate a single-stranded intermediate that corresponds to the leading strand of the DNA. In vivo results have suggested that a palindromic sequence, palA, located near the leading strand termination site acts as the lagging strand origin. In this paper we report the development and characterization of an in vitro system for the replication of single-stranded pT181 DNA. Synthesis of the lagging strand of pT181 proceeded in the absence of the leading strand synthesis and did not require the pT181-encoded initiator protein, RepC. The replication of the lagging strand required RNA polymerase-dependent synthesis of an RNA primer. Replication of single-stranded pT181 DNA was found to be greatly stimulated in the presence of the palA sequence. We also show that palA acts as the lagging strand origin and that DNA synthesis initiates within this region.